The growth of oil palm, cocoa and rice in Malaysia as affected by acid sulfate soil infertility. - Shamsuddin, J.; Auxtero, E. A.; Muhrizal, S.; Totok, Suswanto (2008)
Soils along the coastal plains in Malaysia usually contain pyrite (FeS2). When these areas are drained, pyrite in the sediments oxidizes releasing acidity and A1, and jarosite is formed. This paper summarizes the results of studies on the acid sulface soils planted to oil palm, cocoa and rice. A glasshouse study conducted to test the growth of oil palm on acod sulfate under waterlogged and well drained conditions indicated that the best growth was observed on the non-jarositic freely topsoil. Oil palm was found to be moderatley yolerant to soil acidity. The growth was only affected if A13+ activities were aboved 100uM and pH below 4.3. The result from our study indicated that cocoa was sensitive to the presence of A1 in acid sulfate soil. As the amount of A1 in the cocoa leaves increased, the relative plant height of cocoa seedlings decreased. The critical value for A13+ activities in the soil were 10uM. A study was conducted in the Kelantan Plains, in the Northeast coast state of Peninsular Malaysia to determine the effects of line and organic fertilizer application on rice yield planted on an acid sulfate soil. After applying 4 t of ground magnesium limestone per ha in combination with 0.25 t per ha of organic fertilizer, a rice yield of 7.5 t/ha was obtained in the 2nd season. This is comparable to the rice production in the gragary area of Malaysia. If properly managed, acid sulfate soils in Malaysia can be used for cultivation of oil palm and rice.